Investigation of the Effect of Acceptance and Commitment Therapy on Chronic Pain in the Elderly - Nazari, Zahra (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction and Purpose: The aim of this study was the evaluation of the therapeutic effect of acceptance and commitment of chronic pain in the elderly women of Hamadan. Materials and Methods: The research method was a quasi-experimental research and the research design was pretest-posttest with control group. The population consisted all of women 60–90 years old with chronic pain in Hamedan. The sample of this research consisted of 30 people from the mentioned community. The sample was selected from volunteers who received the highest score in chronic pain questionnaire, and they were randomly divided into control and two experimental groups. The assessment tool is chronic pain questionnaire that includes two numeric measurement scale of pain intensity and physical disability questionnaire. The research data were analyzed through using different methods of descriptive statistics (central tendency and dispersion) and inferential statistics (non-parametric tests such as Kolmogorov–Smirnov, Mann–Whitney, Wilcoxon, and t-test). Findings: The results showed that the treatment based on acceptance and commitment resulted in positive effects on chronic pain, decreasing pain intensity, and reducing physical disability in the elderly (P < 0.05)